Recent Mollusca of Ellsworth County, Kansas - Barry B. Miller; Claude W. Hibbard (Hello World!, 1972)
Thirty-nine species of Mollusca were identified from collections made during 1970 and 1971. Twenty-three of these species represent new records for Ellsworth County. Our material from Ellsworth County and west-central Kansas suggests that a fairly diverse unionid fauna extends farther westward into the state than was previously suspected.